2008
DOI: 10.1063/1.2840118
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of magnetite-containing epitaxial iron oxide films grown on MgO(001) substrates

Abstract: The structural and magnetic properties of three kinds of Fe oxide films—Fe3O4, a berthollide type of Fe oxide, and a composite of Fe3O4 and FeO—grown on MgO(001) substrates epitaxially at 423K by pulsed laser deposition were investigated by magnetoresistance measurement and grazing incidence x-ray diffraction. The Fe3O4 film had the largest negative magnetoresistance and the roughest film-substrate interface. The very close lattice matching of single-phase Fe3O4 and MgO facilitates the formation of antiphase b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Figure 6 shows the (ZFC) magnetization curves obtained during heating for the series of 20 nm films grown at the indicated oxygen pressures. A sharp Verwey transition was found at 121 K, close to the bulk value [31], in of the all films except the two grown under 1 × 10 −6 and 4 × 10 -6 torr oxygen pressure. However, the magnitude of Verwey transition decreases significantly as the oxygen pressure is decreased from 7 × 10 -7 to 5 × 10 -7 torr, and then 3 × 10 -7 torr.…”
Section: Magnetizationsupporting
confidence: 67%
“…Figure 6 shows the (ZFC) magnetization curves obtained during heating for the series of 20 nm films grown at the indicated oxygen pressures. A sharp Verwey transition was found at 121 K, close to the bulk value [31], in of the all films except the two grown under 1 × 10 −6 and 4 × 10 -6 torr oxygen pressure. However, the magnitude of Verwey transition decreases significantly as the oxygen pressure is decreased from 7 × 10 -7 to 5 × 10 -7 torr, and then 3 × 10 -7 torr.…”
Section: Magnetizationsupporting
confidence: 67%
“…2͒ and its characteristic metal-insulator transition at 120 K ͑Verwey transition͒. [3][4][5] Differences between some properties of bulk magnetite and epitaxial thin films have been observed, such as an increased resistivity with decreasing film thickness, [6][7][8] negative magnetoresistance, [9][10][11] decreased and broadened Verwey transition temperature ͑T V ͒, 7,12,13 superparamagnetism in ultrathin films, 14,15 decreased saturation magnetization, [16][17][18][19] and anomalous, planar, and ordinary Hall effects. [20][21][22] This anomalous behavior has often been associated to the film microstructure and the presence of structural growth defects called antiphase boundaries ͑APBs͒.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the Fe 3 O 4 films grow on MgO (100) coherently strained, relaxing partially above a critical thickness, but even for thickness of 700 nm the relaxation is still partial [120,129]. It has been observed that differences exist between some properties of the bulk material and those of epitaxial magnetite films, such as the non saturation of the magnetization at high fields [129,130], decreased and broadened Verwey transition temperature [124,127,128], superparamagnetic behavior of films below 5 nm [131,132], increased resistivity found in epitaxial magnetite films [119,124,133] and large negative magnetoresistance [134][135][136].…”
Section: Structure and Properties Of Epitaxial Fe 3 O 4 Filmsmentioning
confidence: 99%